The Group and Phase Velocity of the Ordinary Wawe in the Ionosphere A Complete Solution and Numerical Analysis - Kurt, Kadri; Yeşil, Melik Buğra; Yıldız, Gülay (My University, 2024)
The ionosphere is a conductive and natural plasma layer of the atmosphere that starts from 50 km above the ground and continues up to approximately 1000 km. To neglect the magnetic field effect on the ionosphere, both vertical and horizontal ionosondes are used to detect the electron density of the ionosphere in many parts of the Earth. In this study, in ionosphere plasma; Without any approximation, the phase and group velocities of the ordinari wave, which is independent of the magnetic field in the collisional ionosphere plasma (electron-ion; electron-neutral), were obtained analyt-ically and its seasonal behavior was calculated numerically. According to the results obtained; There is a strong similarity between the change trends in the phase and group velocities of the ordinari wave at local times of 05:00 in the morning and 20:00 in the evening. It can be said that in these time intervals in the E and F regions of the ionosphere, the wave energy is constant and the directions of the phase and group velocities are in the same direction but in opposite directions.
Keywords: Ionesphrere; Ordinary Wawe; Group-Phase Velocity